Collaboration to Unlock Access : Presentations at the LIBER Conference in ST Petersburg - Friend, Frederick J. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The opportunities provided by open access to journal literature have generated much interest and discussion. LIBER’s approach to this important topic at the St Petersburg Conference was through the theme of collaboration. Each group of stakeholders in scholarly communication, from author through to reader, has an interest in open access. If open access is to be achieved it has to be through collaboration between authors, funding agencies, publishers and librarians working together in the best interests of readers of academic literature. The benefits to individuals and to human society to be gained from open access are described in this quotation from the Budapest Open Access Initiative: "An old tradition and a new technology have converged to make possible an unprecedented public good. The old tradition is the willingness of scientists and scholars to publish the fruits of their research in scholarly journals without payment, for the sake of inquiry and knowledge. The new technology is the internet. The public good they make possible is the world-wide electronic distribution of the peer-reviewed journal literature and completely free and unrestricted access to it by all scientists, scholars, teachers, students, and other curious minds. Removing access barriers to this literature will accelerate research, enrich education, share the learning of the rich with the poor and the poor with the rich, make this literature as useful as it can be, and lay the foundation for uniting humanity in a common intellectual conversation and quest for knowledge." Since calling the meeting which developed the Budapest Open Access Initiative, the Open Society Institute has continued to support discussion and action to implement the two strategies leading to open access identified in Budapest, and the open access session at the LIBER Conference was supported by a grant from OSI.